The Confusion and Reconstruction of the Healthcare-seeking Culture in the Context of China's New Healthcare Reform - Zhipeng HUANG; Zuxun LU; Peigang WANG; Chao WANG (Yixue yu zhexue)
Since the implementation of the new healthcare reforms, China's healthcare industry has achieved significant development. However, pressing issues such as bypassing primary care for specialist visits, preference for high-level medical resources, passive health awareness, and doctor-patient conflicts remain severe. These problems may be attributed to the lag in the construction of residents' healthcare-seeking culture. This paper provides an in-depth analysis of the concept, structural dimensions, and value functions of healthcare-seeking culture. From the dual perspectives of healthcare value cognition and healthcare-seeking cultural choices, it elucidates the profound impact of healthcare-seeking culture on residents' medical behaviors and the order of healthcare-seeking activities. Addressing the current confusion in residents' healthcare-seeking culture, the paper proposes practical approaches, including implementing a hierarchical diagnosis and treatment system, enhancing public education on healthcare culture, fostering harmonious doctor-patient relationships, and optimizing the allocation of medical resources. The aim is to promote the scientific and rational transformation of residents' healthcare-seeking culture, provide new references for regulating social healthcare-seeking order, enhancing public health outcomes, and supporting the implementation of the Healthy China strategy.